Prometheus shackled Goldsmith Banks and England's financial revolution after 1700 - Temin, Peter; Voth, Hans-Joachim. (New York : Oxford University Press, 2013)
Using new archival data from goldsmith banks, Temin and Voth document how government regulation and wartime financing stifled the growth of private credit markets during the Industrial Revolution. They show how, after a turbulent start, banks adapted and found a way to grow, but how the economy at large lost out.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Banks and banking -- Great Britain -- History; Finance -- Great Britain -- History